PENGARUH STRUKTUR KEPEMILIKAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP ENVIRONMENTAL DISCLOSURE PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA - Naufal Azfa Tsaqif; Nurmadi Harsa Sumatra (Komunitas Manajemen Kompetitif, 2026)
Global pressure for corporate environmental transparency continues to intensify, particularly in the energy sector, which contributes substantially to carbon emissions and natural resource exploitation. This study examines the influence of ownership structure-proxied by institutional and managerial ownership-and firm characteristics-proxied by firm size and profitability-on environmental disclosure among energy sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. Agency theory serves as the theoretical foundation, explaining how information asymmetry between principals and agents shapes disclosure behavior. Environmental disclosure is measured using the GRI Standards 300 index comprising 30 environmental disclosure items. A quantitative approach employing multiple linear regression was applied to 173 observations derived from 92 energy sector firms through purposive sampling. Results indicate that institutional ownership and managerial ownership have no significant effect on environmental disclosure, while firm size and profitability exert a positive and significant influence. These findings suggest that internal firm capacity is a more decisive determinant of environmental transparency than ownership-based governance mechanisms, implying the need for more inclusive policy reforms to promote environmental disclosure among smaller and less profitable energy companies in Indonesia.